2019
DOI: 10.1097/md.0000000000014829
|View full text |Cite
|
Sign up to set email alerts
|

Early oral feeding versus traditional feeding after transanal endorectal pull-through procedure in Hirschsprung's disease

Abstract: Our study questioned whether the outcome of postoperative early oral feeding is different from traditional postoperative feeding in children with Hirschsprung's disease who underwent transanal endorectal pull-through.This was an observational and comparative study. Patients were allocated into 2 groups. Age, gender, fever, surgery-related infectious, abdominal distension, bowel obstruction, need for reoperation, peritonitis, anastomosis leak, and abscess formation were assessed. IV fluids and antibiotics usage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The incidence of obstruction was found to be 0%, while that of non-obstruction was 100%. Research Ashjaei et al ( 2019) found the incidence of obstruction was absent, but complaints of abdominal distension were obtained as much as 27%, but statistically, there was no difference [37].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The incidence of obstruction was found to be 0%, while that of non-obstruction was 100%. Research Ashjaei et al ( 2019) found the incidence of obstruction was absent, but complaints of abdominal distension were obtained as much as 27%, but statistically, there was no difference [37].…”
Section: Discussionmentioning
confidence: 97%
“…Research by Ashjaei et al (2019) found the incidence of infection, stenosis, abdominal distension, and fever can occur in Soave and Swenson techniques, but statistically, there is no difference between the two techniques in early feeding on the incidence of stenosis and abdominal distension [37].…”
Section: International Journal Of Scientific Advances Issn: 2708-7972mentioning
confidence: 97%
“…In 18 articles, postoperative ileus was mentioned as an outcome, a definition was provided in eight articles (►Table 3). 14,15,26,27,32,43,46,50,53,57,60,65,67,69,71,72,75,79 One of the articles providing a definition did not report accompanying outcome measures. 57 Of the eight provided definitions, four specified the timeframe of their definition.…”
Section: Reported Outcome Measures For Postoperative Ileusmentioning
confidence: 99%